2017
DOI: 10.1007/s11033-017-4104-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis of alfalfa revealed new salt and drought stress-related factors involved in seed germination

Abstract: Salinity and drought are two major environmental factors that limit the growth and yield of many forage crops in semi-arid and arid regions. Alfalfa (Medicago sativa L.) is one of the most important forage crops in many countries. We aim to investigate the molecular mechanisms of alfalfa in response to salt and drought stresses in this study. Physiological and proteomic analyses were applied to examine the Zhongmu NO.3 alfalfa seed germination stage with 200 mM NaCl and 180 g·L polyethylene glycol (PEG) treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 63 publications
2
26
0
Order By: Relevance
“…It is well-known that salt inhibits soybean seed germination and post-germinative growth, which eventually leads to decreases in yield ( Hamayun et al, 2015 ). Previous investigations and the present study showed that NaCl treatment caused cellular oxidative stress ( Figure 2 ; Liang et al, 2003 ; Zhu, 2016 ; Farhangi-Abriz and Torabian, 2017 ), and the level of cellular oxidative pressure is further associated with the activity of seed germination ( Ma et al, 2017 ). In the past decade, soybean salt tolerance-related quantitative trait loci and some key proteins have been identified over the past few decades ( Xu et al, 2011 ; Guan et al, 2014 ; Kan et al, 2015 ).…”
Section: Discussionsupporting
confidence: 67%
“…It is well-known that salt inhibits soybean seed germination and post-germinative growth, which eventually leads to decreases in yield ( Hamayun et al, 2015 ). Previous investigations and the present study showed that NaCl treatment caused cellular oxidative stress ( Figure 2 ; Liang et al, 2003 ; Zhu, 2016 ; Farhangi-Abriz and Torabian, 2017 ), and the level of cellular oxidative pressure is further associated with the activity of seed germination ( Ma et al, 2017 ). In the past decade, soybean salt tolerance-related quantitative trait loci and some key proteins have been identified over the past few decades ( Xu et al, 2011 ; Guan et al, 2014 ; Kan et al, 2015 ).…”
Section: Discussionsupporting
confidence: 67%
“…Quantitative PCR (qPCR) was performed on a Realplex 4 Master Cycler using a gene-specific primer (Table S1) using Super Real PreMix Plus with Syber Green 1 (TIANGEN Biotech., Beijing, China). Relative gene expression was assessed using a comparative cycle threshold method [40]. The relative gene expression was calculated as follows: 2 −∆∆CT (∆CT = CT, gene of interest -CT versus actin) as described by [41], where the actin gene was used as a reference.…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
“…Moreover, Yacoubi et al (2011 , 2013 ) investigated the impact of PEG imbibition on the alfalfa proteome during seed germination. Ma et al (2017) reported the proteomic changes of germinating alfalfa seeds under PEG and NaCl stresses. Previously reported alfalfa proteomics studies were mainly using two-dimensional gel electrophoresis (2-DE) ( Aranjuelo et al, 2011 ; Yacoubi et al, 2011 ; Yacoubi et al, 2013 ; Atikur et al, 2016 ; Ma et al, 2016 , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“… Ma et al (2017) reported the proteomic changes of germinating alfalfa seeds under PEG and NaCl stresses. Previously reported alfalfa proteomics studies were mainly using two-dimensional gel electrophoresis (2-DE) ( Aranjuelo et al, 2011 ; Yacoubi et al, 2011 ; Yacoubi et al, 2013 ; Atikur et al, 2016 ; Ma et al, 2016 , 2017 ). However, 2D-gel-based approaches had a disadvantage in the identification and accurate quantification of proteins from multiple samples.…”
Section: Introductionmentioning
confidence: 99%